2017
DOI: 10.4103/jrms.jrms_994_15
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of upper lip deficit in patients with cleft lip using dermis fat graft

Abstract: Background:This study aimed to assess dermis fat graft (DFG) as a choice to correct the tissue deficit in the free border of the upper lip in cleft lip repair surgery.Materials and Methods:Thirty-five individuals who referred to Alzahra Hospital at 2013–2014, with lip deformity following the primary repair surgery of cleft lip underwent surgery by DFG technique. Outcomes were assessed 4 months after the surgery based on comparison of preoperative and postoperative photographs.Results:The results in 18 (51.42%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…12 It is also widely recommended to perform overcorrection when using DFGs. 13 Histologic studies on lip augmentation with DFGs have reported normal fatty tissue and vascularized connective tissue without signs of inflammation and necrosis after 11 months. 14,15 However, the absorption rate of DFG is generally reported to be around 15% to 45%.…”
Section: Discussionmentioning
confidence: 99%
“…12 It is also widely recommended to perform overcorrection when using DFGs. 13 Histologic studies on lip augmentation with DFGs have reported normal fatty tissue and vascularized connective tissue without signs of inflammation and necrosis after 11 months. 14,15 However, the absorption rate of DFG is generally reported to be around 15% to 45%.…”
Section: Discussionmentioning
confidence: 99%
“…As lips have a principal aesthetical and functional role in the face [27], it may be questioned whether or not this technique has functional consequences as well. Haneke [28] investigated complications after injection of different types of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…14 For small defects, free flap surgery is relatively too complicated, and free complex tissue grafting may be more suitable. 15 Free scalp grafts have been described for aural stenosis and severe skin lesion 16,17 and can repair the defect with minimum deformity in the donor site. Considering these significant advantages, we introduced a revision of scars and tissue deficiency in the upper lip with free scalp grafting.…”
mentioning
confidence: 99%
“…Free flaps such as temporal artery posterior auricular flaps are suitable for large tissue defects 14 . For small defects, free flap surgery is relatively too complicated, and free complex tissue grafting may be more suitable 15 . Free scalp grafts have been described for aural stenosis and severe skin lesion 16,17 and can repair the defect with minimum deformity in the donor site.…”
mentioning
confidence: 99%